2022
DOI: 10.1212/wnl.0000000000200812
|View full text |Cite
|
Sign up to set email alerts
|

Who to Enroll in Parkinson Disease Prevention Trials?

Abstract: Therapies that prevent the occurrence of Parkinson disease (PD) (primary prevention) or mitigate the progression of symptoms in those with early disease (secondary prevention) are a critical unmet need in disease management. Despite great promise, PD prevention trials have not yet demonstrated success. Initiation of treatment too late in the disease course and the heterogeneity of disease are obstacles that may have contributed to the failure. Genetically stratified groups offer many advantages to primary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Similarly, for LRRK2 carriers, it has been suggested that non-LRRK2 genetic factors may influence PD penetrance [43]. Polygenic risk score (PRS), for instance, was associated with higher penetrance of PD in large cohorts of LRRK2-G2019S carriers [44,45], and the combination of MDS Research Criteria for Prodromal PD with PRS has been proposed for LRRK2-NMC to identify subjects at higher risk [3].…”
Section: Genetic Markers Beyond Gba1 and Lrrk2mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for LRRK2 carriers, it has been suggested that non-LRRK2 genetic factors may influence PD penetrance [43]. Polygenic risk score (PRS), for instance, was associated with higher penetrance of PD in large cohorts of LRRK2-G2019S carriers [44,45], and the combination of MDS Research Criteria for Prodromal PD with PRS has been proposed for LRRK2-NMC to identify subjects at higher risk [3].…”
Section: Genetic Markers Beyond Gba1 and Lrrk2mentioning
confidence: 99%
“…To increase our ability to detect high-risk individuals, clustering clinical and historical data with biochemical markers represents a reasonable option [3].…”
Section: Biochemical Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically defined at-risk populations, as summarized by Niotis et al, 8 provide illustrative examples. The penetrance of many PD pathogenic genetic variants is being estimated with increasing precision.…”
Section: Who (Should Be Enrolled)?mentioning
confidence: 99%
“…Genetically At-Risk Individuals Although many genetic variants have been associated with PD, the 2 that are best positioned for prevention trials are the pathogenic LRRK2 and GBA variants. 20 Prevention studies in genetically at-risk individuals are not unique to PD and are preceded by those in other neurodegenerative diseases, as above, along with other studies in medicine investigating BRCA1 and BRCA2 variants in breast and ovarian cancer, APC variants in familial adenomatous polyposis, and more recently, Phe508del allele carriers in cystic fibrosis. However, studying pathogenic variant carriers in PD does pose some distinct practical and ethical challenges.…”
Section: Whom To Enroll For Pd Prevention Trials?mentioning
confidence: 99%